2017
DOI: 10.1016/j.jpolmod.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Measuring chronic multidimensional poverty

Abstract: This paper adopts a new approach to the measurement of chronic multidimensional poverty. It relies on the counting approach of Alkire and Foster (2011) for the measurement of multidimensional poverty in each time period, and then on the duration approach of Foster (2009) for the measurement of multidimensional poverty persistence across time. The proposed indices are sensitive both to (i) the share of dimensions in which people are deprived and (ii) the duration of their multidimensional poverty experience. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 33 publications
0
31
0
5
Order By: Relevance
“…In addition, future research can explore the temporal nature of poverty within the U.S., adopting approaches similar to those used by Alkire et al. ().…”
Section: Discussionmentioning
confidence: 99%
“…In addition, future research can explore the temporal nature of poverty within the U.S., adopting approaches similar to those used by Alkire et al. ().…”
Section: Discussionmentioning
confidence: 99%
“…The multidimensional approach is an alternative to the monetary-centred approach to poverty and conceptualises poverty in both economic and comprehensive real-life terms. Although there is a danger of conflating poverty with the concept of other dimensions, studies have shown that poverty and well-being are not a single concept and therefore a multidimensional approach is needed for effective policy implementation (Alkire, Apablaza, Chakravarty, & Yalonetzky, 2017;Alkire & Foster, 2007;Axford, 2009;Leu, Chen, & Chen, 2016;Sen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“… In the context of panel data over multiple periods and multiple dimensions, Alkire et al . () consider an approach where an additional cut‐off (triple cut‐off) is adopted to increase the sensitivity of the poverty measure to unequal distributions. We discuss this in more detail in Footnote 4. …”
mentioning
confidence: 99%
“… Our measure can be extended to include the “triple cut‐off” found in Alkire et al . (), though in this application we focus on properties associated with the more familiar dual cut‐off framework of AF. An alternative approach in the static multidimensional framework can be found in Permanyer (); there the “Strong Focus” axiom maintained in the multidimensional poverty measurement literature is relaxed, allowing the welfare of non‐poor households to enter the poverty measure.…”
mentioning
confidence: 99%